2018
DOI: 10.1152/japplphysiol.00114.2018
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of peripheral airway function to changes in FEV1/FVC and RV/TLC with aging

Abstract: Changes in FEV/FVC and RV/TLC are at least, in part, due to changes in peripheral airway function with ageing. Further studies of the relationships between MBNW and standard pulmonary function indices may prove useful for their combined application and interpretation in obstructive airways disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Using an SF6 washout system, Fuchs et al also did not show any relationship between LCI and age up to 20 yrs [29]. On the other hand, lung elasticity declines with age, and this is associated with increases in FEV 1 /FVC, increased trapped gas (RV/TLC), and increases in a number of markers of ventilation heterogeneity including LCI [19]. Kjellberg et al reported on nitrogen-LCI from 400 healthy adult controls up to the age of 71 years, measured using an Exhalyser D device [18].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Using an SF6 washout system, Fuchs et al also did not show any relationship between LCI and age up to 20 yrs [29]. On the other hand, lung elasticity declines with age, and this is associated with increases in FEV 1 /FVC, increased trapped gas (RV/TLC), and increases in a number of markers of ventilation heterogeneity including LCI [19]. Kjellberg et al reported on nitrogen-LCI from 400 healthy adult controls up to the age of 71 years, measured using an Exhalyser D device [18].…”
Section: Discussionmentioning
confidence: 96%
“…Although mean LCI increased with age (0.5 units over 12yrs), this was less than described by Kjellberg in older subjects [18] and, similar to our approach, the authors concluded that a fixed ULN was appropriate. Htun et al and Verbanck et al have separately reported on nitrogen-LCI in similar populations using a different non-commercial nitrogen washout system [19,31,32]. The normal range for LCI in both cases was different, but in contrast to the Exhalyser D data, seemed to show relatively stable ULN for LCI below 40 years, with LCI only increasing above this age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, in older people AHR is predicted by Sacin [78], suggesting the acinar rather than conductive airways contribute to ventilation heterogeneity in older people with asthma. It is worth noting that ventilation heterogeneity increases with age in health [79,80], with an accelerated increase seen in Sacin and LCI after the age of 60 years, versus a steady linear increase in Scond [80,81]. However, Sacin and LCI are both associated with loss of lung elastic recoil in elderly asthma independently of ageing [82].…”
Section: Relationship With Symptoms and Disease Statusmentioning
confidence: 99%
“…And increasing evidence shows that sex, age, and body mass status affect small airway function. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Among the subjects without airflow obstruction, aging is associated with functional small airway abnormality. 3 Changes in FEV1/FVC in healthy adults are associated with the changes in peripheral airway function with aging.…”
Section: Introductionmentioning
confidence: 99%